Removal of Malachite Green from Aqueous Solution by Sargassum wightii - Manikandakumar, N.; Ananthakumar, K. (Asian Journal of Chemistry, 2017)
In present work, the use of Sargassum wightii for the removal of malachite green dye from aqueous solution was studied. Batch adsorption studies were conducted to determine the influence of adsorbent dose, initial dye concentration, pH and temperature. Langmuir, Freundlich and Temkin isotherm models were used to determine the equilibrium isotherm. The adsorption data were fitted on Langmuir isotherm equation. The maximum adsorption capacity was found to be 116.6 mg/g. Thermodynamic analysis of the biosorption proves their spontaneity and endothermic nature. This work reveals that Sargassum wightii algae is low cost alternative source for the removal of malachite green dye from aqueous solution.